Analisis Pengaruh Budaya Organisasi dan Komitmen Organisasi terhadap Kinerja Karyawan yang Dimediasi oleh Kepuasan Kerja - Yuli Anggriyani; Iskandarini Iskandarini (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
The purpose of this study is to analyze the influence of organizational culture and organizational commitment on employee performance mediated by job satisfaction in PT. ABC. The population of this study is all employees working at the mill which amounts to 80 employees. Sample determination is carried out by saturated sampling technique. Data collection is carried out by distributing questionnaires or questionnaires. Data analysis using path analysis. The results of this study show the positive and significant influence of organizational culture on employee performance. Organizational commitment has a positive and significant effect on employee performance. Organizational culture and organizational commitment have a positive and significant effect on job satisfaction and job satisfaction has a significant effect on employee performance.  Furthermore, it is also known that job satisfaction can mediate the relationship between organizational culture and organizational commitment to performance.